TOPSIS dan Double Exponential Smoothing untuk Perangkingan dan Peramalan Penjualan Laptop - Suto Sugiraharjo; Rina Candra Noor Santi (Jurnal Informatika Upgris, 2021)
Problems that occur CV. Mustika Rajawali, which deals with laptop sales ranking and forecasting, is how to predict future laptop sales based on previous sales data. Forecasting is very influential in determining the sales target that must be achieved by CV. Mustika Rajawali. The method has not been used in predicting laptop sales at CV. Mustika Rajawali so that consumers' needs can be seen, whether it has met the sales target or not. The products to be developed in this study are laptop sales ranking and forecasting using the TOPSIS method and double exponential smoothing. To calculate the potential sales as accurately as possible, it can be done using data mining techniques using double exponential smoothing, while the TOPSIS method is used for ranking. Ranking of laptop sales using the TOPSIS method obtained the sales order of Asus A490JA laptops, Asus A409JP, Asus A409MA, Asus E402YA, Asus TP203NAH. Prediction of laptop sales at CV. Mustika Rajawali with a value of α = 0.1 to α = 0.9 obtained the smallest MAE value using α = 0.9, which is 178,237,067 so that the prediction of CV sales. Mustika Rajawali with the exponential smoothing method using a value of α = 0.9.